Hard thin coatings and their applications on C60E non-standard gears - Bošanský, Miroslav (НТУ "ХПІ", 2017)
The article presents the tribological results of laboratory applications five selected thin hard coating on the three materials used in the manufacture of gears. Based on their evaluation in terms of scratch test nanohardness, coefficient of friction, wear resistance, coating thickness and its structure was DLCI coating applied to the gear of the C-C gearing made of material C60E. Thus coated wheels lubricated with organic oils Biohyd MS46 and BioGear S150 were tested for scuffing to the Niemann´s stand. The test results showed that due to the specific conditions for mating gears is not possible to design a coating for gear based on laboratory tests only, but should be based on what the specific requirements for the gear to be applied coating, ie. what type and kind of gearing and on what material wheels.

В статті наведені результати трибологічних лабораторних випробувань п’яти тонких твердих покриттів на трьох матеріалах, які використовуються при створенні зубчатих коліс. Оцінка проводилась по параметрам абразивної наноміцності, коефіцієнта тертя, зносостійкості, товщини покриття та його структури для покриття DLCI, нанесеного на зубчасту шестерню з опукло-увігнутим зачепленням, виготовлену з матеріалу С60Е. Знос даних зубчастих коліс був протестований на стенді Ньюмана з використанням в якості змащування органічних мастил Biohyd MS46 та BioGear S150. Результати випробувань показали, що через особливі умови для зубчастих коліс, які спрягаються, неможливо розробити покриття для зубчатої передачі тільки на основі лабораторних випробувань – необхідно враховувати конкретні вимоги до нанесення покриття, типу та виду передачі а також матеріалу колеса.
Тверді тонкі покриття та їх застосування у нестандартних передачах С60Е
Keywords: scratch test; PVD; hard coating; Niemann´s stend; тверде покриття; зубчасте колесо; стенд Ньюмана